2016
DOI: 10.17795/intjsh-34323
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Noncommunicable Diseases’ Risk Factors Among Secondary School Students in Eastern Iran in 2013

Abstract: Background: Noncommunicable diseases (NCDs) are the main causes of mortality and disability in the world. In order for a campaign against NCDs' risk factors it is necessary to estimate the extent of their prevalence for their decrease through appropriate interventions. Objectives: The aim of this study was to determine the prevalence of NCDs' risk factors among secondary school students in Birjand city, east of Iran. Patients and Methods:In this cross-sectional study, 369 secondary school students aged between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…Adhikari et al [22] and Manita et al [23] steered studies that found hypertension to be more prevalent in men than in women. Similar results were found in a study [24], where 10.6% of study participants were found to be hypertensive.…”
Section: Discussionsupporting
confidence: 91%
“…Adhikari et al [22] and Manita et al [23] steered studies that found hypertension to be more prevalent in men than in women. Similar results were found in a study [24], where 10.6% of study participants were found to be hypertensive.…”
Section: Discussionsupporting
confidence: 91%
“…Considering the prevalence rate of any of the cardiovascular factors that is physical inactivity and unhealthy dietary habits based on two previous studies, the prevalence of the risk factors for the present study was taken to be approximately as 35%. [ 6 7 ] A total number of students in junior college was 1000 and the sample size was calculated by the following formula, n = Z 2 pq N/e 2 (N − 1)+Z 2 pq, taking confidence interval (C.I.) as 95%.…”
Section: S Ubjects and M Ethodsmentioning
confidence: 99%